2018
DOI: 10.1074/jbc.ra118.003116
|View full text |Cite
|
Sign up to set email alerts
|

A d-enantiomeric peptide interferes with heteroassociation of amyloid-β oligomers and prion protein

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects millions of people worldwide. One AD hallmark is the aggregation of β-amyloid (Aβ) into soluble oligomers and insoluble fibrils. Several studies have reported that oligomers rather than fibrils are the most toxic species in AD progression. Aβ oligomers bind with high affinity to membrane-associated prion protein (PrP), leading to toxic signaling across the cell membrane, which makes the Aβ-PrP interaction an attractive therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(80 citation statements)
references
References 77 publications
(109 reference statements)
10
70
0
Order By: Relevance
“…Only a few studies have analyzed the interaction of PrP with Aβ fibrils, or its effect on polymerization or assembly processes. Several different effects of PrP on Aβ aggregation have been described, including inhibition of fibril formation 56 , bundling 57 or fragmentation 58,59 of fibrils, and trapping of Aβ in an oligomeric state within PrP-containing complexes [58][59][60] . In a particularly relevant example, it was reported that protofibrils (like those used here) were the most neurotoxic forms of Aβ in an LTP suppression assay, and were the forms that bound most avidly to PrP 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have analyzed the interaction of PrP with Aβ fibrils, or its effect on polymerization or assembly processes. Several different effects of PrP on Aβ aggregation have been described, including inhibition of fibril formation 56 , bundling 57 or fragmentation 58,59 of fibrils, and trapping of Aβ in an oligomeric state within PrP-containing complexes [58][59][60] . In a particularly relevant example, it was reported that protofibrils (like those used here) were the most neurotoxic forms of Aβ in an LTP suppression assay, and were the forms that bound most avidly to PrP 21 .…”
Section: Discussionmentioning
confidence: 99%
“…These assemblies have a size of a few micrometers as determined by dynamic light scattering and show cloud-like morphologies as seen by atomic force microscopy 33 . The Aβ:huPrP stoichiometry of the hetero-assemblies depends on the PrP concentration added to Aβoligo and reaches a value of 4:1 (monomer ratio) in the presence of an excess of either huPrP or huPrP 33 .…”
Section: Introductionmentioning
confidence: 98%
“…Several in vitro studies on the Aβ-PrP interaction suggest that Aβoligos bind at two Lys-rich parts (residues 23 to 27 and ≈ 95 to 110) on PrP [28][29][30][31][32][33] , but an additional involvement of the Cterminus of PrP has also been suggested 14 . A structural study of insoluble PrP C -Aβoligo complexes described this as a "hydrogel", in which the A oligomers were rigid, while PrP still has high molecular mobility 34 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations